(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Cardiovascular diseases are the leading causes of mortality in the world today with hypertension being the major clinical presentation of these diseases. This study assessed the anti-hypertensive effects of Lagenaria breviflora whole fruit and Xanthsoma sagittifolium corms in experimentally inudced hypertensive Wistar rats. The ability of the plants to ameliorate oxidative damage accompanying hypertension was evaluated using changes in oxidative stress markers as well as monitoring of cardiovascular parameters. Hypertension was induced by intraperitoneal injection of DOCA salt twice weekly and daily inclusion of NaCl (1%) in drinking water. Methanol extracts of L.breviflora or X. sagittifolium was administered to hypertensive rats for 35 days and the outcome was compared to hypertensive rats administred with lisinopril or hydrochlorothiazide and a group of normotensive rats (control). Systolic, diastolic and mean arterial pressures were determined on day 34 and blood sample collected on day 35. The rats were thereafter humanely sacrificed, and organs were harvested. This study showed that the extracts lowered blood pressure, free protein thiols but increased toal protein, gluthathione peroxidase, reduced glutathione, glutathione S-transferase, catalase and nitric oxide in the heart, kidney and liver compared to untreated hypertensive rats. However, malondialdehyde levels and hydrogen peroxide activities were reduced. L. breviflora fruit and X. sagittifloium corm exhibited antihypertensive properties and ameliorate oxidative damage associated with hypertension by enhancing the antioxidant defense sysyem and inhibiting generation of free radicals.